PLACE ATTACHMENT DAN PRO-ENVIRONMENTAL BEHAVIOUR DI KALANGAN SISWA SMP DI SAMARINDA - Sari, Firda Yunita Kartika; Nuryadin, Atin; Komariyah, Laili (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2024)
Research on place attachment (an individual's emotional bond with their environment) and pro-environmental behavior (attitudes and actions to protect the environment) is important to understand how an individual's emotional bond with their environment can influence pro-environmental behavior, especially for students. This study aims to evaluate the level of place attachment and pro-environmental behavior among junior high school students in Samarinda and examine the correlation between the two variables. This study used a quantitative approach with survey techniques. The research sample consisted of 378 junior high school students in Samarinda who were randomly selected. Data were collected using questionnaires. The results showed that the level of place attachment of junior high school students in Samarinda was 3.75 which was categorized as moderate, while the level of pro-environmental behavior was 3.58 which was also categorized as moderate. A positive but very low correlation existed between place attachment and pro-environmental behavior. This study shows the importance of considering place attachment factors in developing approaches to improve pro-environmental behavior among secondary school students.